Extracts from writers on international law (s.n., 1898)
All of the texts extracted here support the British position viz-à-viz the Venezuelan border arbitration. There is no indication of source, but from similarities in typography and binding it would appear that this text was created by the British Foreign Office, and that it was printed in London, by Harrison and Sons, in 1898.